Regional Variation of the Minimum Wages in China - Chunbing Xing; Jianwei Xu (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the regional variation of minimum wage in China. We first introduce the institutional background of China's minimum wage policy, and then describe the regional variation of the minimum wages using detailed minimum wage data since the late 1990s. Large regional variation exists in the period studied, and the regional variation has been declining since the late 1990s. Economic factors, including GDP, economic structure, consumption level, are the main determinants for the large regional variation in the minimum wages. There is weak evidence suggesting that the regional variation is influenced by political factors, such as competition of local officials.
Keywords: J3; E2; 330; minimum wage; regional variation; China